2020
DOI: 10.1364/oe.394580
|View full text |Cite
|
Sign up to set email alerts
|

Above 25 nm emission wavelength shift in blue-violet InGaN quantum wells induced by GaN substrate misorientation profiling: towards broad-band superluminescent diodes

Abstract: We report a thorough study of InGaN quantum wells spatially modified by varying the local misorientation of the GaN substrate prior to the epitaxial growth of the structure. More than 25 nm shift of emission wavelength was obtained, which is attributed to indium content changes in the quantum wells. Such an active region is promising for broadening of the emission spectrum of (In,Al,Ga)N superluminescent diodes. We observed that the light intensity changes with misorientation, being stable around 0.5° to 2° an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13][14][15] Recently, attempts using substrates with local off-angle patterning have been proposed for InGaN-based multiwavelength light emitters. [16][17][18][19][20][21] Well-designed 3D shapes of photoresists are transferred to GaN surfaces, forming local off-angle distributions. A remarkable feature of this method is that not only stable planes exposed in the 3D structures by SAG but also unstable planes can be used.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15] Recently, attempts using substrates with local off-angle patterning have been proposed for InGaN-based multiwavelength light emitters. [16][17][18][19][20][21] Well-designed 3D shapes of photoresists are transferred to GaN surfaces, forming local off-angle distributions. A remarkable feature of this method is that not only stable planes exposed in the 3D structures by SAG but also unstable planes can be used.…”
mentioning
confidence: 99%
“…This finding is consistent with previous reports. [26][27][28]34) Additionally, the wider wavelength shift mentioned above is attributed to the larger In composition variation (>10%) compared to that (4.5%) of the previous report. 27) This is most likely due to the larger maximum offangle.…”
mentioning
confidence: 54%
“…InGaN-based multiwavelength light emitters utilizing local off-angle variation have already been demonstrated. [24][25][26][27][28] Dróżdż et al fabricated InGaN LEDs on (0001) GaN surfaces with several hundreds of μm-scale patterns formed by grayscale photolithography and dry etching. 27) The local offangle ranges from 0.3 to 2.4°.…”
mentioning
confidence: 99%
“…Representative planes include the (0001), {11 22}, and {1 101}. On the other hand, multiple research groups have reported that planes slightly tilted from the (0001) plane (⩽∼5 • ) reduce the In compositions in InGaN quantum well (QW) emitters [48][49][50][51][52][53][54]. This property has led to these materials being used in broadband superluminescent diodes [50,52] and polychromatic LEDs [51,54].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, multiple research groups have reported that planes slightly tilted from the (0001) plane (⩽∼5 • ) reduce the In compositions in InGaN quantum well (QW) emitters [48][49][50][51][52][53][54]. This property has led to these materials being used in broadband superluminescent diodes [50,52] and polychromatic LEDs [51,54]. Interestingly, these 3D structures are formed artificially and can be composed of arbitrary unstable planes, thereby enhancing the structural controllability and, eventually, the spectral controllability.…”
Section: Introductionmentioning
confidence: 99%